Precision dicing of hard materials with abrasive blade - Araujo, L. A. O.; Foschini, C. R. [UNESP]; Jasinevicius, R. G.; Fortulan, C. A. (Springer, 2016)
The present work shows the experiments on dicing of high alumina substrates using abrasive blades. The technology used by modern electronic components is based on narrow and thin ceramic and single crystal substrates. One of the techniques used to obtain these products is to dice a larger substrate using an abrasive blade to generate low damages and high productivity called dicing process. Samples with high alumina (99.8 %) were diced with diamond abrasive blades in a creep feed process. The process parameters were changed as cuts 1 to 3 mm deep were made. The feed speed varied from 1 to 19 mm/s and the blade rotation varied from 10,000 to 30,000 rpm. The blade wearing as well as the linearity and the quality of dicing were analyzed. Higher blade rotation increases the blade stiffness and on these experiments a more stable cutting process was achieved at 30,000 rpm. The removal material mechanism was also explored comparing the chipping between silicon and the high alumina specimens.
Keywords: Precision dicing; Dicing saw; Dicing machine; Abrasive cutting process